2019
DOI: 10.1016/j.cell.2019.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Neural Activity across the Brains of Socially Interacting Bats

Abstract: Social interactions occur between multiple individuals, but what is the detailed relationship between the neural dynamics across their brains? To address this question across timescales and levels of neural activity, we used wireless electrophysiology to simultaneously record from pairs of bats engaged in a wide range of natural social interactions. We found that neural activity was remarkably correlated between their brains over timescales from seconds to hours. The correlation depended on a shared social env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 98 publications
(144 reference statements)
12
132
0
Order By: Relevance
“…This parameter determines the scope of the self and implements the continuum leading smoothly from cell-> body-> swarm. Signaling between animals in an ecosystem (Pais- Vieira et al, 2013;Kingsbury et al, 2019;Zhang and Yartsev, 2019) is not fundamentally different than signaling within the brain -both are examples of information propagating through a network of locally-competent micro-agents. Others have pointed out the parallels between the dynamics of cancer and ecosystem-level degradation (Degregori and Eldredge, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This parameter determines the scope of the self and implements the continuum leading smoothly from cell-> body-> swarm. Signaling between animals in an ecosystem (Pais- Vieira et al, 2013;Kingsbury et al, 2019;Zhang and Yartsev, 2019) is not fundamentally different than signaling within the brain -both are examples of information propagating through a network of locally-competent micro-agents. Others have pointed out the parallels between the dynamics of cancer and ecosystem-level degradation (Degregori and Eldredge, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent social neuroscience studies have reported interactions between the brains of a group of members measured as inter-brain synchronization (e.g., phase synchrony). This synchrony can be enhanced during intense socialization, body or speech coordination, music production, dancers, student-teacher interactions in classrooms, touch-mediated pain reduction, creativity in cooperative tasks, and even in socially interacting bats (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Hence, it can be a metric for more effective group interactions.…”
Section: Team Flow As a Bonafide Inter-brain Statementioning
confidence: 99%
“…The normalized power was calculated through subtracting the individual's mean PSD from the PSD at each condition. The normalized power was averaged within the following frequency bands: delta (1 -3 Hz), theta (4 -7 Hz), alpha (8)(9)(10)(11)(12), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), gamma (31 -120 Hz), and lower gamma (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). The normalized power for the 128 channel data and the permutation statistics with Bonferroni multiple comparison correction was projected to topographical maps using EEGLAB toolbox.…”
Section: Power Spectrum Analysismentioning
confidence: 99%
“…So far, only few studies accomplished the combination of electrophysiology with vocalization production in bats [7][8][9] . Other studies in freely moving bats have been performed before, but using megachiropterans ("non-laryngeal echolocators") as animal model [31][32][33] .…”
mentioning
confidence: 99%
“…Classical functions of gamma rhythms across species are linked to selective attention, cortical computation and working memory 45 . In bats, changes in gamma power have been linked to the processing of auditory stimulation in the bat auditory cortex and to social interaction in frontal areas 31,46 . Moreover, an increase in gamma power was found in the superior colliculus after the production of clusters of echolocation calls in freely flying bats 7 .…”
mentioning
confidence: 99%